Determinants Of Taxpayer Compliance In Paying Property Tax In Palembang City - Melati, Ima; Novalia, Nurkardina; Emilda, Emilda (Journal of Management, Economic, and Accounting, 2025)
The main objective of this study is to evaluate the impact of the quality of tax knowledge, the application of tax sanctions, and the level of individual awareness on public compliance in fulfilling their obligations to pay taxes on land and buildings in the city of Palembang. The focus of the respondents in this study is taxpayers residing in Seberang Ulu I District, totaling 1,370 people. The sample size was determined using the Slovin formula, with respondents selected using random sampling without stratification, resulting in 93 participants. The analytical techniques used include quantitative descriptive analysis and multiple linear regression testing. In this study, the independent variables consist of tax literacy, penalties for tax violations, and fiscal awareness, while the level of compliance in paying taxes serves as the dependent variable. Partial testing indicates that neither tax literacy nor tax awareness has a strong relationship with compliance behavior. However, in the combined analysis, the three variables collectively had a significant influence on fiscal compliance behavior. It is hoped that the results of this study can be used as a reference by government agencies in improving the quality of tax services to build taxpayer satisfaction and trust, particularly in the city of Palembang